2002
DOI: 10.1063/1.1450051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the number of wells on optical and structural properties in InGaN quantum well structures grown by metalorganic chemical vapor deposition

Abstract: High-quality InGaN quantum well (QW) structures with one, two, three, five, and seven wells were grown by metalorganic chemical vapor deposition. The effect of the number of InGaN QWs on the structural and optical properties was studied by high-resolution x-ray diffraction (HRXRD), atomic force microscopy, low excitation density photoluminescence (PL), high excitation density pulsed PL, and PL excitation (PLE). The 10 K PLE band edge of all the samples is almost same, but the 10 K PL peaks of the InGaN QWs ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Many investigations have been performed on the influence of dislocations on the electrical, optical, and structural properties of GaN and related materials, as these materials are grown on lattice-mismatching Al 2 O 3 or SiC substrates and high density of threading dislocations always exist within the films [1][2][3][4][5][6][7][8][9] It is well known in the case of light emitting devices based on conventional compound semiconductor materials that dislocations act as a strong nonradiative recombination center and have significant detrimental effects on the emission properties [10]. In the case of GaN-based devices, however, contradicting results have been reported on effects of the dislocations [1 -9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations have been performed on the influence of dislocations on the electrical, optical, and structural properties of GaN and related materials, as these materials are grown on lattice-mismatching Al 2 O 3 or SiC substrates and high density of threading dislocations always exist within the films [1][2][3][4][5][6][7][8][9] It is well known in the case of light emitting devices based on conventional compound semiconductor materials that dislocations act as a strong nonradiative recombination center and have significant detrimental effects on the emission properties [10]. In the case of GaN-based devices, however, contradicting results have been reported on effects of the dislocations [1 -9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that Raman shift of the E 2 and the E 1 phonons [5], carrier mobility [2], and reverse-bias leakage current of p -n junction [6] are also affected by the dislocations. Furthermore, it was proposed that dislocations are responsible for the fluctuation in In composition and interface roughness, which in turn affects PL intensity and position of the GaN/InGaN multi quantum well (MQW) structure [7].…”
Section: Introductionmentioning
confidence: 99%
“…The fact of strong emission from InAlGaN in comparison with that of AlGaN is considered to be due to the fact that the excited carriers move into the In-rich region and recombine radiatively rather than be trapped in the nonradiative centers generated by defects [16]. However, the variation in potential fluctuation and indium segregation may be caused by the variation in dislocation density and interface roughness with an increasing number of wells [11]. From the element composition list in Table 1, we observed that the spatial indium fluctuations enriched and the exciton localization effect gradually enhanced with increasing pairs of quantum wells, resulting from indium segregation regions acting as quantumdot-like structures.…”
Section: Resultsmentioning
confidence: 95%
“…The reason is that the carrier lifetime tends to increase as the temperature rises [9]. Furthermore, the temperature-induced blueshift of the emission peak can be demonstrated by the band-tail model with a Gaussian-like distribution of the density of states and the screening effect of the piezoelectric field [10,11].…”
Section: Introductionmentioning
confidence: 96%
“…The surface roughness of sample D was 1.31 nm, and that of sample E was 4.103 nm. These results show that not only the surface morphology became rougher, but the size of pits became larger with increasing the number of MQW pairs, which could be attributed to the thickness and indium compositional fluctuations of MQWs and, therefore, result in the redshift of PL emission wavelength [7] as well as the increase in FWHM of bandedge emission.…”
Section: Methodsmentioning
confidence: 87%